Additional effects of topical tranexamic acid in on-pump cardiac surgery - Noppon Taksaudom (2018)
© The Author(s) 2016. Objective Postoperative bleeding after cardiac surgery is commonly associated with hyperfibrinolysis. This study was designed to evaluate the efficacy of topical tranexamic acid in addition to intravenous tranexamic acid in reducing bleeding in cardiac surgery cases. Methods From July 1, 2014 to September 30, 2015, 82 patients who underwent elective on-pump cardiac surgery were randomized into a tranexamic acid group and a placebo group. In the tranexamic acid group, 1 g of tranexamic acid dissolved in 100 mL of normal saline solution was poured into the pericardium during sternal closure; the placebo group had 100 mL of saline only. Two patients were excluded from the study due to obvious surgical bleeding. The primary endpoint was total blood loss 24 h after surgery. Repeated measures with mixed models was used to analyze bleeding over time. Results There was no significant difference in demographic and intraoperative data except for a significantly lower platelet count preoperatively in the tranexamic acid group (p = 0.030). There was no significant difference in postoperative drainage volumes at 8, 16, and 24 h, postoperative bleeding over time (coefficient = 0.713, p = 0.709), or blood product transfusion between the groups. There were no serious complications. Conclusions Topical tranexamic acid is safe but it adds no additional efficacy to the intravenous application in reducing postoperative blood loss. Intravenous tranexamic acid administration alone is sufficient antifibrinolytic treatment to enhance the hemostatic effects during on-pump cardiac surgery.